2006
DOI: 10.1159/000089721
|View full text |Cite
|
Sign up to set email alerts
|

Study on Cardioactive Effects of Brazilein

Abstract: Brazilein (6a,7-dihydro-3,6a,10-trihydroxy-benz[b]indeno[1,2-d]pyran-9(6H)-one) is a compound obtained in a large amount from Caesalpinia sappan ethanol extracts with a high purity of about 98%. In isolated cardiac tissues, we found that brazilein exhibited a positive inotropic action in a concentration-dependent manner with little effect on heart rate and coronary perfusion. To study its possible mode of action, isolated rat hearts were treated with propranolol. This treatment did not alter the cardiotonic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…A previous study showed that the extract of Caesalpinia sappan Linn., which has long been used in traditional medicine as a hemostatic and anti-inflammatory agent in China [3,4], induced cell death in head and neck cancer cells [5]. Brazilein, a compound obtained in a large amount from the dried heartwood of Caesalpinia sappan Linn., has some pharmacological activities such as cardioactive effects as a potential inotropic drug [6]. But its anti-tumor effect has never been demonstrated.…”
mentioning
confidence: 99%
“…A previous study showed that the extract of Caesalpinia sappan Linn., which has long been used in traditional medicine as a hemostatic and anti-inflammatory agent in China [3,4], induced cell death in head and neck cancer cells [5]. Brazilein, a compound obtained in a large amount from the dried heartwood of Caesalpinia sappan Linn., has some pharmacological activities such as cardioactive effects as a potential inotropic drug [6]. But its anti-tumor effect has never been demonstrated.…”
mentioning
confidence: 99%
“…In isolated cardiac tissues, brazilein exhibited a positive inotropic action in a concentration-dependent manner with little effect on heart rate and coronary perfusion. Also brazilein, produced its positive inotropic effect through inhibiting Na + , K + -ATPase and could thus serve as a structural paradigm to develop new inotropic drugs [76].…”
Section: Found Inmentioning
confidence: 99%
“…These include Cardiovascular Drug Review [15], Circulation [16], Circulation Research [17], Hypertension Research [18], Journal of Cardiovascular Pharmacology [19,20], Journal of Hypertension [12,13,21], Journal of Lipid Research [22], Journal of Molecular and Cellular Cardiology [23], Life Sciences [24][25][26][27][28], Molecular Pharmacology [29], Neurology Research [30], Pharmacology [31], Pharmacology Research [32], and Vascular Pharmacology [33,34]. Chinese cardiovascular pharmacology has finally gained a respectable profile on the world stage.…”
Section: Chinese Research In Cardiovascular Pharmacologymentioning
confidence: 99%